PERBANDINGAN KEDUDUKAN DAN PERANAN WANITA DALAM SISTEM KELUARGA IE JEPANG DAN SISTEM KELUARGA TRADISIONAL BATAK TOBA - dhaher f pasaribu (Jurnal Pustaka Nusantara dan Budaya, 2013)
Toba society know the same kinship system that is patrilineal kinship (the line age of men).The result of this system affect the status and role of women in the family. But even though embraced the same same kinship system, tradisional Japanese society (Ie) and tradisional Batak Toba society have different views about it. All data obtained with the library research and searching from the internet. To compare this, the author use comparative theory approaches and methods of sociology analyst with women's studies object. The purpose of this study is to Describe, how it compares status and role of women in traditional Japanese family system (Ie) and traditional Batak Toba as a children, a mothers, wives in a family, and whatever background behind it. After searching, the author found results that this research indicate that there is a difference beetwen role and position of women in traditional Japanese family system and traditional Batak Toba family system. The women in the ie family is lower, while batak toba have more high status eventhough they are have an equall embracing patrilineal system, but they have different views.